Exploring the recognition behavior of a fluorescein-based probe towards the significant detection of Cu2+ and Zn2+ ions: Experimental and computational studies - Kumar N.; Sada P.K.; Kundan A.K.; Bar A.; Jassal A.K.; Rai S.P.; Singh V.K.; Garg N.; Singh A.K.; Singh A.K.; Kumar S.; Singh L.; Rai A. (My University, 2025)
A new fluorescein hydrazone (FA1) has been synthesized employing fluorescein hydrazide and 3,5-diiodosalicylaldehyde and its complete physiochemical characterization have been carried out. A single crystal XRD studies of FA1 has been performed. Among the tested metal ions FA1 significantly detects Cu2+ and Zn2+ in EtOH/H2O (8:2, v/v)). There is an emergence of a new absorbance peak at λmax 431 nm with Cu2+ ions. A “turn-on” behavior in fluorescence at λem510 nm was observed with Zn2+ ions owing to chelation enhanced fluorescence. This act of spectrophotometric changes and naked eye color variation from colorless to yellow is because of coordination with the metal ions rather than most common opening of spirolactum ring. FA1-Cu2+ and FA1-Zn2+ensembles display reversible behavior with EDTA2− ions. In a study on latent fingerprint detection using powder compounds, it was found that FA1 and FA1–Zn2+ showed excellent adherence to finger ridges and produced clear features without any background stains. The Hirshfeld surface and fingerprint analysis of FA1 offer a detailed examination of pairwise interactions between atoms. Additionally, topological analysis of FA1 has been conducted using NCI, AIM, ELF, and LOL methodologies. Alamar assay of FA1 on HEK-293 cell lines exhibited biocompatibility with minimal cytotoxicity. Hence, they were effectively applied for live cell imaging for intracellular sensing of Cu2+ and Zn2+ in HEK-293 cells. © 2025 Elsevier B.V.